Relative Importance of THM Effects during Non-isothermal Fluid Injection in Fractured Media - Jalali, R.; Evans, K.; Valley, Benoît; Dusseault, M.B. (: American Rock Mechanics Association, 2015)
Rock mass treatment using fluid injection is common in various industrial applications, including enhanced recovery methods in the oil and gas industry, rock mass pre-conditioning in the mining industry, and heat extraction in geothermal systems. Non-isothermal fluid injection requires consideration of the thermomechanical perturbation as well as hydro-mechanical processes. Thermal effect is rarely included in injection analysis for geothermal application and thermal enhanced oil recovery methods, although with long times their impact becomes of first-order. In this paper, a fully-coupled, hybrid numerical model is implemented to study the effect of cold fluid injection into a conductive fracture under different injection/cooling schemes. The results show that the thermoelastic effect soon overwhelms the hydroelastic effect adjacent to the injection source, whereas far from the injection point, hydroelastic effect dominates because the pressure front always moves faster than the cold front. In addition, the fracture becomes more susceptible to shear failure in the presence of both thermoelastic and hydroelastic induced stresses for the case of cold fluid injection. The magnitude of the changes implies that an appropriate thermo-hydromechanical (THM) model is an essential key to address the physical behavior and potential impairment of fracture conductivity under thermal stimulation.
, 2015